Local Genius dalam Drama dan Teater Putu Wijaya: Local Genius in Putu Wijaya's Drama and Theater - Purwanto Lephen; Senowarsito Senowarsito (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This research aims to uncover and analyze the elements of local genius (local wisdom) that form the foundation of the aesthetics and philosophy in Putu Wijaya's dramaturgy. The research method employed is descriptive, with a hermeneutic approach, conducted through textual analysis of play scripts, such as Aduh, Edan, and Zero, as well as observation of the rehearsal process and performances of the "theatre starting from what is available" or "New Tradition" technique, which he pioneered. The findings indicate that the local genius in Putu Wijaya's works is not merely a symbolic use of Balinese or Indonesian cultural elements, but is internalized in the form of: a non-linear and cyclical dramaturgical structure, reflecting the cosmological concept of time in the Indonesian archipelago; a conflict that presents a paradigm of "chaos" as a creative energy, aligning with the concepts of Rwa Bhineda (the duality of opposites) and Desa-Kala-Patra (place-time-context); and an intimate relationship between the audience and the performers (Puyung ma isi), which revives the participatory spirit of traditional performances. In conclusion, Putu Wijaya's approach to drama and theatre is a contemporary form of local genius that transforms traditional values into a universal stage language while remaining firmly rooted in cultural identity.